2022
DOI: 10.1097/hp.0000000000001650
|View full text |Cite
|
Sign up to set email alerts
|

Electron Paramagnetic Resonance Measurements of Lifetime Doses in Teeth of Durham Region Residents, Ontario

Abstract: The Canadian Nuclear Safety Commission (CNSC) and Ontario Power Generation (OPG) determined the total dose contribution of nuclear power plants in Durham Region populations by analyzing environmental samples from the surrounding areas of both nuclear generating stations (Pickering and Darlington). However, the total doses from the various sources were unknown in Durham Region populations, Ontario. Electron paramagnetic resonance (EPR) dosimetry with tooth enamel has been successfully established as an effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
(99 reference statements)
0
7
0
Order By: Relevance
“…Tooth enamel is the only human tissue capable of recording radiation doses throughout life and measuring doses ranging from low to high using EPR spectrometers. The minimum detection limit found in tooth enamel using EPR dosimetry (X-band), as per the literature, is <100 mGy (down to 30 mGy) (Ghimire and Waller 2023;Hayes et al 1998;Shishkina et al 2016). However, the actual detection limit depends on how experiments are conducted.…”
Section: Low Dose Measurements In Epr Tooth Enamel Dosimetrymentioning
confidence: 77%
See 3 more Smart Citations
“…Tooth enamel is the only human tissue capable of recording radiation doses throughout life and measuring doses ranging from low to high using EPR spectrometers. The minimum detection limit found in tooth enamel using EPR dosimetry (X-band), as per the literature, is <100 mGy (down to 30 mGy) (Ghimire and Waller 2023;Hayes et al 1998;Shishkina et al 2016). However, the actual detection limit depends on how experiments are conducted.…”
Section: Low Dose Measurements In Epr Tooth Enamel Dosimetrymentioning
confidence: 77%
“…These studies have indicated the necessity for EPR tooth enamel dosimetry standardization to improve dose calibration. To this end, increasing measurement accuracy and reproducibility can be accomplished by removing impurities (dentin) from the tooth enamel using chemical and mechanical methods, employing highly sensitive EPR resonators, and using background subtraction, among other techniques (Ghimire and Waller 2023). Most importantly, unlike many modern instruments, EPR spectrometers are designed and built within a tradition primarily for use by specialists and are not intended to be foolproof.…”
Section: Human Tooth As a Biological Dosimetermentioning
confidence: 99%
See 2 more Smart Citations
“…The equipment used is a Bruker EMXmicro X-Band EPR spectrometer. The technique has been used to measure physical doses near CANDU NPPs using tooth samples obtained from local dentists (Ghimire and Waller 2023a) and also yielded numerous approaches to improve sensitivity and decrease the lower limit of detection (Ghimire and Waller 2023b, c, d). Low dose non-human biota studies have been conducted on a variety of shelled aquatic species near and of interest to nuclear facilities in Canada (Gough et al 2022).…”
Section: Researchmentioning
confidence: 99%